Arranjos institucionais entre o poder público municipal e instituições privadas para oferta de vagas na educação infantil - Oliveira, Jaqueline Dos Santos [UNESP]; Borghi, Raquel Fontes [UNESP] (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2013)
This paper features a research of the partnerships/agreements between the municipal public services and the private sphere to the offer of vacancies in Early Education, in the large counties of São Paulo. The study allowed us to identify different arrangements between the municipal public service and private institutions, which 30 of the 54 large counties of São Paulo turn to the services from partnerships as a mean to attend the local demand, including the institutions with lucrative purposes, being different of the traditional forms of partnerships instituted in Early Education. The text is based on the literature analysis about the theme and the information collected during the research from phone calls to municipal administrators, municipal official sites and government sites.

Apresenta um mapeamento das parcerias/convênios entre o poder público municipal e a esfera privada para a oferta de vagas na educação infantil nos municípios paulistas grandes. O estudo permitiu identificar diferentes arranjos institucionais entre o poder público municipal e as instituições privadas, em que 30, dos 54 municípios paulistas grandes, recorrem ao atendimento conveniado como forma de atender a demanda local, inclusive com instituições de finalidade lucrativa, diferenciando-se das tradicionais formas de convênios instituídas na educação infantil. O texto baseia-se na análise de literatura sobre a temática e os dados coletados durante a pesquisa, a partir de contatos telefônicos direto com os gestores municipais, sites oficiais dos municípios e sites governamentais.
Institutional arrangements between the municipal public service and private institutions to the offer of vacancies in Early Education
Keywords: educação infantil; parcerias público-privadas; oferta de vagas; convênios; Early Education; public-private partnerships; offer of vacancies; agreements